Nacionalismo e talento individual em Mário de Andrade: ambivalências de um projeto poético-crítico - Santos, Nubia Silva dos (2011)
This study is based in the discussion of the conditions of creation of the Brazilian literary nationalism, from the intellectual talent of Mario de Andrade, who amidst the clash of the order of being or not being nationalist linked this to another struggle not less important: to be or not to be a pedagogical person. This is because the critic has assumed to himself the incumbency to dialogue with young Brazilian writers and intellectuals, through the profitable exchange of correspondences about the central problems of constitution of the art of Brazilian orientation, the Brazilian nationality and about the genuinely Brazilian culture. In this regard, we highlight the correspondence of Mário de Andrade with Carlos Drummond de Andrade, the first poet is from São Paulo and was in the middle of an effervescence of technological, cultural, political, economical and esthetic development, symbol of progress; and the other one is from Minas Gerais, and was ―isolated‖ between the landscapes of the provincial of Belo Horizonte symbol of backwardness. Thus, what we aims to carry through this work is not properly a study of the poetry of Mario de Andrade or Drummond, what we will research is in such a way the poet Mario de Andrade, through his ―interested‖, social, conscious and active art makes his poetic project of nation and of national identity, which is consistent with the vision of Brazil from specific Brazilian intellectuality. The cutting made, the reading of the letters that had established a profound dialogue between Mário de Andrade and Drummond, is a methodological choice because similar dialogue also happened between the critical poet Mário de Andrade and lots of other writers, poets, young Brazilian authors, that retook after the Republic announcement, slavery abolition, beginning of the capitalist economic market, beginning of industrialization and progress the cultural, economical, social and literary politics arguments around the necessity of the construction of their nationality, of being Brazilian, or as said by Mário de Andrade: of ―their Brazilian soul‖.